Uji Aktivitas Antijamur Nanopartikel Zink Oksida (ZnO) Ekstrak Kulit Jengkol terhadap Candida Albicans - Ica Dwi Patricia; Vera Estefania Kaban; Astriani Natalia Br Ginting (Yayasan Literasi Sains Indonesia, 2026)
Natural materials are increasingly being used as sources of bioactive chemicals due to increased concerns about safety, sustainability, and environmental effect. Jengkol peel is one such natural material with potential because it contains various secondary metabolites compounds that have biological activity. On the other hand, Candida albicans fungal infections remain a health problem, while conventional antifungal options are limited and have the potential to cause side effects. Zinc oxide (ZnO) nanoparticles are known to have broad antimicrobial activity, and their synthesis can be carried out in an environmentally friendly manner through a green synthesis approach using natural materials. This study aims to test the antifungal activity of ZnO nanoparticles synthesized using jengkol peel extract against Candida albicans. The study was conducted experimentally. Antifungal activity was tested using the well diffusion method with various concentrations of ZnO nanoparticles. The results showed the formation of an inhibition zone around the well, indicating the antifungal activity of ZnO nanoparticles. The increase in ZnO nanoparticle concentration is directly proportional to the increase in inhibition zone diameter, with the highest inhibition of 14 mm categorized as moderate activity. This study proves that jengkol-based ZnO nanoparticles have the potential to be developed as an environmentally friendly alternative antifungal agent.